Parental Relationships, Patient-Centered Communication With Healthcare Providers, and Diabetes Management Across Emerging Adulthood - Berg, Cynthia A; Campbell, MaryJane Simms; Kent de Grey, Robert G; Butner, Jonathan E; Murray, Mary; Wiebe, Deborah J (Journal of pediatric psychology, 2022)
To examine whether yearly fluctuations in acceptance from and disclosure to parents were associated with fluctuations in perceptions of patient-centered communication (PCC) with the healthcare provider and whether fluctuations in PCC were associated with self-efficacy, type 1 diabetes self-care, and HbA1c across four annual assessments during early emerging adulthood (EA). A total of 228 high school seniors (M age = 17.76 years at time 1) reported on mothers' and fathers' acceptance and diabetes-related disclosure to parents, diabetes self-care, and PCC once per year for 4 years. HbA1c was collected from assay kits. Multilevel models revealed within-person associations such that in years when individuals reported greater maternal acceptance than their average, they reported higher PCC. In addition, between-person differences indicated that individuals who reported more maternal acceptance on average relative to others also perceived greater PCC. Similar associations were found for EAs' reports of fathers. No significant effects were found for disclosure to either mother or father. Yearly fluctuations in PCC were associated with self-efficacy such that in years when perceived PCC was higher, self-efficacy was higher. Between person-effects were found for self-efficacy, self-care, and HbA1c such that individuals who reported more PCC on average relative to others reported higher self-efficacy, better self-care, and lower HbA1c. Aspects of EA's relationships with parents fluctuate with perceptions of PCC with healthcare providers. Perceived PCC with the healthcare provider may be important in higher self-efficacy, diabetes self-care, and lower HbA1c across the early EA years.